Cryopreservation of infectious Cryptosporidium parvum oocysts - Justyna J. Jaskiewicz (Nature Portfolio, 2018)
Research on Cryptosporidium parasites, a major cause of acute infant diarrhea, is hampered by the short shelf life of oocysts, thus requiring routine propagation in laboratory animals. Here, the authors report a method to cryopreserve viable and infectious Cryptosporidium oocysts by ultra-fast cooling.